Digital patient-reported outcomes in inflammatory bowel disease routine clinical practice: the clinician perspective - Amalie Søgaard Nielsen; Charlotte W. Appel; Birgit Furstrand Larsen; Lisa Hanna; Lars Kayser (SpringerOpen, 2022)
Abstract Background Use of digital health services, such as digital patient-reported outcomes, depends on many different human factors as well as digital design solutions. One factor is clinicians' attitude towards the system, their reasoning behind the using system and their perceptions of patients' ability to engage with digital health systems. This study aimed to explore hospital clinicians' attitudes towards digital patient-reported outcomes used in the routine care and treatment of inflammatory bowel disease, and to explore the potential role of clinicians' attitudes in influencing patients' use of digital patient-reported outcomes. Results Twelve clinicians using digital patient-reported outcome assessments in the care of inflammatory bowel disease were interviewed about their experiences of, and perspectives on, using this service. Most participants supported the use of digital patient-reported outcome assessments in the care of most patients. Participants reported that most patients found the digital solution easy to use. They perceived digital patient-reported outcomes to have three main purposes: prioritising resources; improving patients' quality of life; and improving quality of care. The patient-clinician relationship was of great importance to participants. Participants varied in their intention to use digital PRO, as some viewed the system as a positive but optional add-on for patients, whilst others intended to use the system with all eligible patients. Conclusion Clinicians' general support of using digital patient-reported outcomes might facilitate their use among patients with inflammatory bowel disease. The participants saw benefits in doing so for patients, clinicians and the wider health service. Clinicians' attitudes towards the use of digital PRO in the care of their patients may influence patients' uptake of health service.